The Use of Hi-Fix in Indian Waters - Moraes, A. G. (The International Hydrographic Review, 2015)
Until the early sixties, hydrographic surveys in Indian waters were carried out by the classical method of position fixing with the use of sextant angles and station pointer. This necessitated extensive triangulation, building up of a number of sounding marks on the land and, often, laying of beacons at sea to extend the positioning control seaward. Beyond such extensions, position fixing was dependent on dead reckoning and astro fixes in surveying ships. Accurate hydrographic surveying was therefore restricted in range to good visibility, daylight hours and fair weather conditions up to about 15 miles from the coast. In areas of strong tidal currents, such as the Gulf of Kutch, Gulf of Cambay and Hugli River, position fixing and sounding on pre-planned lines was exceedingly difficult, and surveys could not always be completed satisfactorily without loss of time. The advent of Hi-Fix heralded a new era in hydrographic surveys around India. This portable and precise Radio Position-Fixing Aid, with ability to provide two-range or hyperbolic mode fixes accurately at long range, enabled the hydrographic surveying organisations to undertake surveys with precision at considerable distance from the mainland, at all hours of the day. Thus, during the last 10 years the Hydrographic Department has used 3 Hi-Fix chains for hydrographic surveys. One of these chains has also been used successfully for acceptance trials of newly built ships. Each of the major ports at Bombay, Madras, Calcutta and Vishakhapatnam have permanently sited Hi-Fix or Sea-Fix chains for dredging and survey control. The Oil and Natural Gas Commission has a Hi-Eix chain with which off-shore waters have been explored for oil and gas, and the Geological Survey of India has recently acquired such a sysieia for mineral exploration off-shore. The successful use of Hi-Fix equipment in Indian waters may be seen from figure 1. Some of the areas shown have permanently sited chains lor regular resurveys. The coverage of these waters with precision surveys in large areas, up to 50-60 miles from the coast, has been possible largely due to the availability of Hi-Fix. This paper summarises the experience of various organisations in the use of Hi-Fix in Indian waters, and highlights points of special interest to surveyors.